1993
DOI: 10.1002/pc.750140508
|View full text |Cite
|
Sign up to set email alerts
|

Application of dynamic mechanical analysis for the study of the interfacial region in carbon fiber/epoxy composite materials

Abstract: The application of dynamic mechanical analysis (DMA) for quantifying interfacial interactions in composites is briefly reviewed. Carbon fiber/epoxy composites with fiber volume fractions of 12, 17, 38 and 61 vol% were subjected to flexural deformation on a Dupont DMA 983 instrument. The dependencies of dynamic mechanical properties of the composites on experimental parameters such as oscillation mode, amplitude, frequency, and temperature were investigated. As opposed to the storage modulus, the loss modulus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(115 citation statements)
references
References 15 publications
(8 reference statements)
3
110
0
2
Order By: Relevance
“…Silane-treated OPMF composites showed lower damping than unmodified OPMF composites. As the damping at the interface increases, the interfacial adhesion between fibers and matrix becomes weaker (Dong and Gauvin 1993). Tan δ results indicated that silane-treated OPMF formed good interfacial adhesion with the matrix in hybrid composites, as composites with strong interfacial bonding tend to dissipate less energy compared with composites with poor interfacial bonding.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 84%
“…Silane-treated OPMF composites showed lower damping than unmodified OPMF composites. As the damping at the interface increases, the interfacial adhesion between fibers and matrix becomes weaker (Dong and Gauvin 1993). Tan δ results indicated that silane-treated OPMF formed good interfacial adhesion with the matrix in hybrid composites, as composites with strong interfacial bonding tend to dissipate less energy compared with composites with poor interfacial bonding.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 84%
“…It is worth pointing out that the tan δ curves in Figure 6b provide not only the T g values of both the evaluated composite laminates, but also express their damping ability, which can be inferred from the magnitude of the tan δ peak [32]. Several studies have shown that the magnitude of tan δ in continuous fiber-reinforced polymer matrix composites is inversely proportional to the fiber/matrix mergence [33,34]. It can, therefore, be concluded from T g values and peak heights of the tan δ curves depicted in Figure 6b that a stronger bond between the CF and epoxy matrix phases was achieved by incorporating the MFC hierarchical substructure directly onto the originally unsized-CF framework before the RIFT process.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…Among many research works, parameter B which corrects the volume fraction of reinforcement because of the formation of a layer of immobilized interphase resulting from strong interactions at the interface is the particularly worth mentioning one conducted by Dong and Gauvin [22]. Therefore, we chose the parameter B to evaluate the interfacial adhesion between the fibers and matrix.…”
Section: Dynamic Mechanical Analysis Of the Compositesmentioning
confidence: 99%